2020
DOI: 10.1016/j.pcad.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cardiovascular disease among people living with HIV in sub-Saharan Africa

Abstract: As longevity has increased for people living with HIV (PLWH) in the United States and Europe, there has been a concomitant increase in the prevalence of cardiovascular disease (CVD) risk factors and morbidity in this population. Whereas the availability of HIV antiretroviral therapy has resulted in dramatic increases in life expectancy in sub-Saharan Africa (SSA), where over two thirds of PLWH reside, if and how these trends impact the epidemiology of CVD is less clear. In this review, we describe the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 188 publications
(176 reference statements)
0
34
2
Order By: Relevance
“…Adequate training of physicians and pharmacists is essential to deal with increasingly complex cases across Africa given the increasing prevalence of diseases and patients with co-morbidities [ 7 , 52 , 53 , 54 , 55 ]. This is seen as particularly important during the COVID-19 pandemic given the extent of misinformation that exists regarding possible medicines for the prevention and treatment of COVID-19 and their consequences [ 9 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate training of physicians and pharmacists is essential to deal with increasingly complex cases across Africa given the increasing prevalence of diseases and patients with co-morbidities [ 7 , 52 , 53 , 54 , 55 ]. This is seen as particularly important during the COVID-19 pandemic given the extent of misinformation that exists regarding possible medicines for the prevention and treatment of COVID-19 and their consequences [ 9 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…The astronomic rise in cardiovascular disease (CVD) burden on the African continent coupled with high infectious disease burden, such as HIV, imposes a considerable burden on the fragile health systems and developing economies in this region [14]. Contemporary data on the rising burden of CVDs such as type 2 DM among PLWH, in particular, are needed to understand its determinants and propose solutions to address this double burden of disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings appear to contradict previous studies that suggested HIV individuals had a higher CVD burden. (21)(22)(23) However, because of the complete dependence on physician diagnosis and missing diagnoses of prevalent cardiovascular problems frequent in HIV, such as atherosclerotic illnesses, our ndings should be interpreted with caution. Previous needs assessments in public health facilities, particularly regional referral hospitals, revealed a lack of diagnostics capability for screening and diagnosing major NCDS, such as CVDs, which may explain our low incidence in these settings.…”
Section: Discussionmentioning
confidence: 87%